Sexual offenders discharged from prison in England and Wales: a 21-year reconviction study - Cann, Jenny (Legal and criminological psychology, 2004)
Purpose. This study examined the reconviction rates of a cohort of sexual offenders released from prison in England and Wales during 1979. A 21-year follow-up period was used and sexual, violent and general reconvictions assessed. Method. The sample consisted of all adult male sexual offenders discharged from prison in England and Wales during 1979 (N = 419). Criminal conviction histories were obtained for the sample from the Offenders Index and sexual, violent and general reconvictions were calculated, over a period of 21 years (1979-2000). Results. A quarter (24.6%) of the sample received a reconviction for a sexual offence over the 21-year follow-up period, 21.7% received a violent reconviction and 61.8% received a general reconviction. A proportion of the sample received their first sexual reconviction 5, 10 or 15 years after being discharged from custody, thus remaining at risk of reconviction for many years. Conclusions. The findings from this study give a unique insight into the long-term offending of discharged sexual offenders in England and Wales and have implications for the supervision of such offenders.